Differential impact of risk factors on stroke occurrence among men versus women in West Africa The SIREN Study (2019)
Background and Purpose—The interplay between sex and the dominant risk factors for stroke occurrence in sub-Saharan Africa has not been clearly delineated. We compared the effect sizes of risk factors of stroke by sex among West Africans. Methods—SIREN study (Stroke Investigative Research and Educational Networks) is a case-control study conducted at 15 sites in Ghana and Nigeria. Cases were adults aged >18 years with computerized tomography/magnetic resonance imaging confirmed stroke, and controls were age- and sex-matched stroke-free adults. Comprehensive evaluation for vascular, lifestyle, and psychosocial factors was performed using validated tools. We used conditional logistic regression to estimate odds ratios and reported risk factor specific and composite population attributable risks with 95% CIs. Results—Of the 2118 stroke cases, 1193 (56.3%) were males. The mean±SD age of males was 58.1±13.2 versus 60.15±14.53 years among females. Shared modifiable risk factors for stroke with adjusted odds ratios (95% CI) among females versus males, respectively, were hypertension [29.95 (12.49–71.77) versus 16.1 0(9.19–28.19)], dyslipidemia [2.08 (1.42–3.06) versus 1.83 (1.29–2.59)], diabetes mellitus [3.18 (2.11–4.78) versus 2.19 (1.53–3.15)], stress [2.34 (1.48–3.67) versus 1.61 (1.07–2.43)], and low consumption of green leafy vegetables [2.92 (1.89–4.50) versus 2.00 (1.33–3.00)]. However, salt intake and income were significantly different between males and females. Six modifiable factors had a combined population attributable risk of 99.1% (98.3%–99.6%) among females with 9 factors accounting for 97.2% (94.9%–98.7%) among males. Hemorrhagic stroke was more common among males (36.0%) than among females (27.6%), but stroke was less severe among males than females. Conclusions—Overall, risk factors for stroke occurrence are commonly shared by both sexes in West Africa favoring concerted interventions for stroke prevention in the region.